2017
DOI: 10.2147/ppa.s130985
|View full text |Cite
|
Sign up to set email alerts
|

Patient adherence to subcutaneous IFN beta-1a injections using the RebiSmart<sup>&reg;</sup>&nbsp;injection device: a retrospective real-world study among Dutch and German patients with multiple sclerosis

Abstract: PurposeLong-term treatment adherence among patients with multiple sclerosis (MS) is a general concern, with an established correlation with clinical efficacy. Closely monitoring patients’ treatment behavior may have a beneficial effect on adherence. This study assessed adherence, in daily life, to subcutaneous (sc) IFN beta-1a, self-administered using the RebiSmart® electronic injection device (the IFN beta-Ia autoinjector device), in patients with MS.Patients and methodsThis was a retrospective observational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…RebiSmart ® (Merck, Zug, Switzerland) is an electronic injection device for use by multiple sclerosis patients. It was the first electromechanical autoinjector for multiple sclerosis patients [ 22 ], and has reported adherence rates of 95% across a median drug exposure period when the device is used for 979 days [ 23 25 ]. There is evidence suggesting that technologized injection devices may increase the rates of adherence to use of biologics.…”
Section: Discussionmentioning
confidence: 99%
“…RebiSmart ® (Merck, Zug, Switzerland) is an electronic injection device for use by multiple sclerosis patients. It was the first electromechanical autoinjector for multiple sclerosis patients [ 22 ], and has reported adherence rates of 95% across a median drug exposure period when the device is used for 979 days [ 23 25 ]. There is evidence suggesting that technologized injection devices may increase the rates of adherence to use of biologics.…”
Section: Discussionmentioning
confidence: 99%
“…Adherence to injectable DMTs and other interventional strategies is usually considered inferior in MS patients [10][11][12][13][14][15][16]; a retrospective study of MS patients initiating therapy with 1 of 4 injectable DMTs found that after 18 months, 11.2% of patients switched their medication, and 33.9% discontinued their treatment [17]. An adherence study on ambulatory patients carried out in Spain showed that after 2 years of starting DMT, INF-β was discontinued in 9.9% of patients, after 5 years discontinuation rose to 41.2% and after 8 years discontinuation rate was 58.7% [18].…”
Section: Plos Onementioning
confidence: 99%
“…Electronic auto-injection device (RebiSmart1; Merck Serono S.A.-Geneva, Switzerland, a branch of Merck Serono S.A., Coinsins, Switzerland, an affiliate of Merck KGaA, Darmstadt, Germany) was developed for the subcutaneous administration of IFN-β1a [10][11][12][13][14]20]. The device simplifies the injection process and help patients to overcome injection-related issues, thereby possibly increasing adherence to treatment.…”
Section: Plos Onementioning
confidence: 99%
“…High levels of treatment adherence among multiple sclerosis patients have been reported in studies examining the use of electronic injection devices that are similar to the e-Device evaluated in the current study; for example, allowing patients to individually adjust settings, such as injection speed and depth, and having the ability to electronically store data such as date and time of injections [ 32 34 ]. Consistent with these studies in multiple sclerosis, patients with rheumatic diseases recruited to provide their input on the e-Device in the current study reported high levels of e-Device acceptability and high levels of empowerment in the heiQ, SUTAQ, and eHLQ questionnaire.…”
Section: Discussionmentioning
confidence: 99%